Impact of Animal Disease Outbreaks and Alternative Control Practices on Agricultural Markets and Trade The case of FMD - Junker, Franziska (OECD Publishing, 2009)
Foot and Mouth Disease (FMD) is one of the most contagious animal diseases. Because of the easy transfer between animals, FMD is of importance to the domestic market, but also to international agricultural trade. Infected countries are often confronted with rigorous measures implemented by their trading partners. The guidelines set out by the World Organization for Animal Health (OIE) define the waiting period after which a country that experienced an FMD epidemic can be declared as free of the disease for international trade purposes. In order to minimize the duration of this period, infected developed countries have often implemented mass slaughter strategies. The aim of the paper is to examine the impact of alternative control strategies on the domestic market of the infected country and on international markets. The paper provides a description of the different options for policy intervention in case of a FMD epidemic. It gives an overview of the history of FMD in OECD and selected non-OECD countries including the policy measures taken to fight the disease. A quantitative assement combining the Aglink-Cosimo and the GTAP model is presented
Keywords: Agriculture and Food